Pengaruh Pemberian Puding Kurma Susu Rendah Lemak Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Anisa Dwi Rachmawati; Gurid Pramintarto Eko Mulyo; Yenny Moviana; Yohannes Willihelm Saleky; Jedya Lucas A. Purba (Jurnal Gizi dan Dietetik, 2026)
Potassium and calcium have the potential to lower hypertension. Food sources of potassium and calcium are found in foods such as dates and low-fat milk, which are often made into pudding. This study aimed to determine the effect of low-fat milk and date pudding on lowering blood pressure in hypertensive patients in the Pasirkaliki Community Health Center (Puskesmas) area in Cimahi. The design used was a quasi-experimental two-group pretest-posttest with control group design. The study subjects were 30 hypertensive patients aged 26–65 years. They were divided into a treatment group, given 240 g of pudding daily, with 120 g each in the morning and evening, and a control group, given DASH diet education once for 7 consecutive days. The sampling technique used purposive sampling. The results showed a decrease in systolic blood pressure in the treatment group, with an average of 132.66 mmHg to 129.6 mmHg, a decrease of 3.06 mmHg, but the decrease was not significant (p=0.104), and an increase in diastolic blood pressure, with an average of 84.6 mmHg to 85.86 mmHg, a decrease of 1.26 mmHg, indicating a non-significant increase (p=0.504). In the control group, there was an increase in systolic blood pressure, with an average of 132.86 mmHg to 135.33 mmHg, a 2.47 mmHg increase, but this increase was not significant (p=0.396), and a decrease in diastolic blood pressure, with an average of 85.66 mmHg to 84.6 mmHg, indicating a non-significant decrease (p=0.575). The results showed no significant difference in the reduction of systolic (p=0.107) and diastolic (p=0.433) blood pressure between the treatment and control groups. It is recommended that longer-term interventions be conducted, taking into account the dosage.